La rivière Magpie-Mutehekau shipu en personne - Fabienne Joliet; Azou Joliet-Bidet (EchoGéo)
The Mutehekau Shipu or Magpie is the third river in the world to become a legal entity under international law. It flows through Quebec's North Shore into the St. Lawrence River. Reacting to the fate of its "big sister", the nearby Romaine River, which has just been harnessed by four large hydroelectric dams, the Magpie's destiny had other plans: it has been protected as a legal person since 2021. On a regional and Quebec scale, this is a first that testifies to a synergy between natives (Innu) and non-natives, a strategy of environment and decolonization; on an international scale, it is a third that refers to a paradigm shift and an environmental genuine ontological turning point. This case study is illuminated by the fieldwork and stories collected.